The Integration of General Education in the Academic Programme to Enhance the Self-Efficacy of Accounting Students at a South African University - Suntharmurthy Kristnasamy Naidoo; S. Govender (Journal of Education and Vocational Research, 2020)
The purpose of this paper is to investigate the impact of General Education in enhancing the Self-efficacy of Cost and Management Accounting (CMA) students to assess whether Self-efficacy, is having any positive influence on the students’ academic performance. The research design for this paper was descriptive, longitudinal and a mixed-method approach. The nature of the quasi-experimental approach that was used in the current paper is a non-equivalent pre-test and post-test control group design. The target population was CMA students. A census survey was conducted. Findings, which were analysed with the aid of descriptive statistics, indicate a significant correlation in the post-test (Self-efficacy) scores of the group that undertook the General Education Modules and not the group that did not undertake the General Education Modules. This paper recommends the implementation of General Education skills into the curriculum and a model to measure Self-efficacy of students. Moreover, these skills appear to be very poor amongst current learners and respondents believed that Self-efficacy could have a positive effect on the academic performance of learners.